DESAIN DAN ANALSIS RANGKA PADA MESIN PENGUPAS BIJI KOPI BASAH MENGGUNAKAN SOFTWARE SOLIDWORKS - Eko Aprianto Nugroho; Abdul Rahman Agung Ramadhan (Jurnal Teknik dan Science, 2023)
Coffee is a commodity that is currently developing. However, many coffee farmers in remote areas experience problems in increasing their business along with high market demand due to a lack of business support tools. The purpose of this paper is to find out the materials used in designing a wet coffee bean peeler machine. Design the frame of a wet coffee bean peeler machine using Solidwork software. Wet coffee bean peeler analysis. The type of iron to be used in the frame of this wet coffee bean peeler is galvanized angle iron with a size of 22 x 22 x 1.8 mm. The results obtained show that the von misses stress calculated using solidworks has the greatest stress of 69,654 Mpa. For von misses stress by manual calculation, a value of 71.707Mpa is obtained. The results obtained show that the displacement calculated using solidworks has the greatest stress of 0.293 mm. For displacement with manual calculations, a value of 0.163 mm is obtained. The results obtained show that the Factor of Safety value calculated using Solidworks has the greatest stress of 2,928 ul. For the Factor of Safety with manual calculations, a value of 2,830 ul was obtained.